An intrinsic DFF40/CAD endonuclease deficiency impairs oligonucleosomal DNA hydrolysis during caspase-dependent cell death: a common trait in human glioblastoma cells. Issue 7 (10th January 2016) - Sánchez-Osuna, María; Martínez-Escardó, Laura; Granados-Colomina, Carla; Martínez-Soler, Fina; Pascual-Guiral, Sònia; Iglesias-Guimarais, Victoria; Velasco, Roser; Plans, Gerard; Vidal, Noemi; Tortosa, Avelina; Barcia, Carlos; Bruna, Jordi; et al.
Abstract: Background: Glioblastoma (GBM) or grade IV astrocytoma is one of the most devastating human cancers. The loss of DFF40/CAD, the key endonuclease that triggers oligonucleosomal DNA fragmentation during apoptosis, has been linked to genomic instability and cell survival after radiation. Despite the near inevitability of GBM tumor recurrence after treatment, the relationship between DFF40/CAD and GBM remains unexplored. Methods: We studied the apoptotic behavior of human GBM-derived cells after apoptotic insult. We analyzed caspase activation and the protein levels and subcellular localization of DFF40/CAD apoptotic endonuclease. DFF40/CAD was also evaluated in histological sections from astrocytic tumors and nontumoral human brain. Results: We showed that GBM cells undergo incomplete apoptosis without generating oligonucleosomal DNA degradation despite the correct activation of executioner caspases. The major defect of GBM cells relied on the improper accumulation of DFF40/CAD at the nucleoplasmic subcellular compartment. Supporting this finding, DFF40/CAD overexpression allowed GBM cells to display oligonucleosomal DNA degradation after apoptotic challenge. Moreover, the analysis of histological slices from astrocytic tumors showed that DFF40/CAD immunoreactivity in tumoral GFAP-positive cells was markedly reduced when compared with nontumoral samples. Conclusions: Our data highlight the low expression levels of DFF40/CAD and the absence of DNA laddering as common molecular traits in GBM. These findings could be of major importance for understanding the malignant behavior of remaining tumor cells after radiochemotherapy.